Bletilla striata polysaccharide-coated andrographolide nanomicelles for targeted drug delivery to enhance anti-colon cancer efficacy - Yue, Zhongqun; Zhu, Yue; Chen, Teng; Feng, Tingting; Zhou, Ying; Zhang, Jiaojiao; Zhang, Ning; Yang, Jing; Luo, Gang; Wang, Zuhua (Frontiers in Immunology, 2024)
Background: Vitamin E, which is also known as tocopherol, is a compound with a polyphenol structure. Its esterified derivative, Vitamin E succinate (VES), exhibits unique anticancer and healthcare functions as well as immunomodulatory effects.Natural polysaccharides are proved to be a promising material for nano-drug delivery systems, which show excellent biodegradability and biocompatibility. In this study, we employed a novel bletilla striata polysaccharide-vitamin E succinate polymer (BSP -VES) micelles to enhance the tumor targeting and anti-colon cancer effect of andrographolide (AG).Methods: BSP-VES polymer was synthesized through esterification and its structure was confirmed using 1H NMR. AG@BSP-VES was prepared via the dialysis method and the drug loading, entrapment efficiency, stability, and safety were assessed.Furthermore, the tumor targeting ability of AG@BSP-VES was evaluated through targeted cell uptake and in vivo imaging. The antitumor activity of AG@BSP-VES was measured in vitro using MTT assay, Live&Dead cell staining, and cell scratch test.In this study, we successfully loaded AG into BSP-VES micelles (AG@BSP-VES), which exhibited good stability, biosafety and sustained release effect. In addition, AG@BSP-VES also showed excellent internalization capability into CT26 cells compared with NCM460 cells in vitro. Meanwhile, the specific delivery of AG@BSP-VES micelles into subcutaneous and in-situ colon tumors was observed compared with normal colon tissues in vivo during the whole experiment process (1-24 h). What's more, AG@BSP-VES micelles exhibited significant antitumor activities than BSP-VES micelles and free AG.The study provides a meaningful new idea and method for application in drug delivery system and targeted treatment of colon cancer based on natural polysaccharides.